Reimagining Singapore Self and Society in Contemporary Art - Lum, Chee-Hoo; Lizeray, Juliette Yu-Ming; Twardzik Ching, Chor Leng (Springer Nature Singapore : Imprint: Springer, 2023)
XVII, 287 p. 68 illus., 60 illus. in color.